Kinematic analysis of the women's 400m hurdles - Guex, K. (New Studies in Athletics, 2012)
The women's 400m hurdles is a relatively new discipline and a complex event that cannot be approached as a "simple" 400m "decorated" with ten hurdles. It is, of course, fundamental to develop physical qualities such as speed, strength and endurance, but it is also essential to develop technical and tactical aspects. Literature on the biomechanics of the 400m hurdles, which would guide this development, is relatively sparse. Moreover, the existing studies have analysed only a few kinematic parameters. The aim of this study was to observe different kinematic parameters in women 400m hurdlers of different performance levels in order to describe the management and structure of this discipline. Based on the video observation of 46 female athletes competing at a national meeting in France and the 2011 IAAF World Championships in Athletics, it provides among other things an analysis of stride length, stride frequency, velocity, distribution of effort and the structure of the race. A large range of performance levels was analysed (from 52.47 sec to 71.39 sec) in order to identify the most relevant biomechanical parameters and to isolate the most important ones for world-class performance.